Integration of Ki Hadjar Dewantara's Educational Values in Digital Ski Learning at MAN 4 Sleman - Wahyu Sihab; Sri Haningsih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines technology based teaching methods for Islamic Cultural History (SKI) at MAN 4 Sleman from the perspective of Ki Hajar Dewantara's teaching methods. This study uses a qualitative approach based on a systematic literature review and collects data from various historical literature, classical Islamic education, and current academic sources. The results of the study indicate that the transformation of SKI learning in the digital era not only highlights technological advances but also emphasizes the importance of character building and moral values among students. Although digital media such as LMS, interactive videos, and infographics have been used, the aforementioned approach remains informative and lacks context and reflection. Ki Hajar Dewantara's educational philosophy, encompassing the trilogy of education “Ing Ngarso Sung Tulodo,” “Ing Madyo Mangun Karso,” and “Tut Wuri Handayani,” is crucial in developing an SKI learning model that is not only cognitively robust but also socially effective and resilient.